PENGARUH PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PENGHASILAN PASAL 21 (ORANG PRIBADI) PADA PT. DWITAMA GLOBAL PERSADA TAHUN 2018-2021 - Ezra Hasundungan Doloksaribu; Lorina Siregar Sudjiman (Jurnal Ekonomis, 2022)
The purpose of this study is to analyze individually and collectively the effect of understanding on the compliance of taxpayers with income tax article 21 (individuals). This study uses respondents by conducting 39 people who are taxpayers who work at PT. DWITAMA GLOBAL PERSADA, and using the SPSS (Statistical Package for the Social Sciences) program. The data collection method used Taken sampling in the form of a questionnaire with a Likert scale of 1-5 points. Data analysis methods include Descriptive Statistics, Validity Test, T Test, F Test, Reliability, Simple Linear and Correlation Coefficient Test. The results showed that the understanding of taxpayers and compliance with income tax article 21 (individuals) at PT. DWITAMA GLOBAL PERSADA showed very good results. And also shows that the understanding of taxpayers has a significant effect on compliance with article 21 income tax payers (individuals).